Deutero-Isaiah, J and P: Who is in the image and likeness of God? Implications for אדם and theologies of creation - Quine, C (Taylor and Francis, 2015)
This article aims to bring together the discussions surrounding creation and humanity in Isaiah 40-55 and Genesis 1,26. The article demonstrates that Deutero-Isaiah’s view of humanity is incompatible with that of the P narrative, rendering attempts to cite it in support of Genesis 1 ineffective. It argues that the application of the terms in Genesis 1,26 to Seth alone of Adam’s sons in Genesis 5, suggests a program of election, or selection, necessary to counter the theological difficulties raised by potentially stating that Israel’s enemies were also made in the image of God. The theological implications for understanding humanity’s position in the cosmos are evident. The inclusiveness with which theologians have tended to read Gen 1,26-27 (as applicable to all humanity) is called into question.